1999
DOI: 10.1038/sj.cdd.4400507
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide-induced activation of c-jun N-terminal kinase (JNK) correlates with drug-induced apoptosis in salivary gland acinar cells

Abstract: We have examined the ability of etoposide to induce apoptosis in two recently established rat salivary acinar cell lines. Etoposide induced apoptosis in the parotid C5 cell line as evidenced by the appearance of cytoplasmic blebbing and nuclear condensation, DNA fragmentation and cleavage of PARP. Etoposide also induced activation of c-jun N-terminal kinase (JNK) in parotid C5 cells by 4 h after treatment, with maximal activation at 8 - 10 h. Coincident with activation of JNK, the amount of activated ERK1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 46 publications
1
57
0
Order By: Relevance
“…[43][44][45] We have previously reported that in salivary epithelial cells, apoptosis induced by etoposide or TPA correlates with sustained activation of JNK. 15,46 Treatment of parotid C5 cells with etoposide resulted in the activation of JNK in 4-6 h, which was maintained throughout the time course of apoptosis, 46 while treatment of parotid cells with TPA resulted in a biphasic activation of JNKs with the later phase commencing by 4 h. 15 In the current studies, we extend these observations to show that sustained activation of JNK also occurs in parotid C5 cells induced to undergo apoptosis by inhibition of PKCa. Activation of JNK occurred as early as 12 h after transduction and was maximal at 18-24 h (data not shown).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…[43][44][45] We have previously reported that in salivary epithelial cells, apoptosis induced by etoposide or TPA correlates with sustained activation of JNK. 15,46 Treatment of parotid C5 cells with etoposide resulted in the activation of JNK in 4-6 h, which was maintained throughout the time course of apoptosis, 46 while treatment of parotid cells with TPA resulted in a biphasic activation of JNKs with the later phase commencing by 4 h. 15 In the current studies, we extend these observations to show that sustained activation of JNK also occurs in parotid C5 cells induced to undergo apoptosis by inhibition of PKCa. Activation of JNK occurred as early as 12 h after transduction and was maximal at 18-24 h (data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…47 In contrast to the JNK pathway, most studies indicate that activation of extracellular regulated kinases (ERKs) protects against apoptosis, 31,48,49 while more limited data suggest a role for ERK activation in promoting apoptosis. [50][51][52] Indeed, we have previously shown that ERK is inactivated in parotid C5 cells induced to undergo apoptosis by treatment with etoposide 46 or TPA. 15 However, the data presented in the current manuscript show that apoptosis associated with PKCa inhibition correlates with an increase in the expression of ERK1 and ERK2 protein as well as an increase in the abundance of the phosphorylated or activated forms of these kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Although our original studies have focused upon etoposideinduced apoptosis, 39,40 we have recently demonstrated that other drugs are also able to induce apoptosis in the rat salivary acinar cell line C5. Both taxol and brefeldin A have been demonstrated to induce apoptosis of the C5 cell line.…”
Section: Igf1 Treatment Suppressed Apoptosis Induced By Other Agentsmentioning
confidence: 99%
“…29,[36][37][38] The data in Figure 1 clearly indicated that IGF1 induced potent, long-lasting activation of Akt, and we examined the ability of IGF1 to suppress apoptosis induced by etoposide in salivary acinar cells. It has been previously demonstrated that etoposide induces apoptosis of the C5 cell line and that this apoptosis was correlated with the activation of JNKs, 39 inhibition of basal ERK activation, 39 and activation of PKCd. 40 As a marker of apoptosis, we chose to quantitate caspase 3 activation and DNA fragmentation since these changes are detectable at 8 h after treatment of C5 cells with etoposide 39 and maximal levels of activated Akt were still present at this time point (Figure 1b, lane 10).…”
Section: Igf1 Treatment Suppressed Apoptosis Induced By Etoposide In mentioning
confidence: 99%
See 1 more Smart Citation